(untitled) (Research, Society and Development, 2022)
The objective was to identify the morphometric variables that contribute to the dissimilarity between the species Butia exilata Deble & Marchiori and Butia lallemantii Deble & Marchiori using Euclidean analysis. For this purpose, 11 genotypes of the species B. exilata, from the city of Sarandi, RS (population 1) and 33 genotypes of the species B. lallemantii from the cities of São Francisco de Assis, RS (population 2), Manoel Viana, RS (population 3) and Alegrete, RS (population 4) were used. Twelve characters were measured: plant height (PH), leaf length (LL), leaflet length (CFO), number of leaflets (NFL), number of fruits per infructescence (NFI), fruit mass (FM), fruit longitudinal diameter (FLD), fruit equatorial diameter (FED), pyrenic mass (PM), pyrenic longitudinal diameter (PLD), pyrenic equatorial diameter (PED) and mesocarp mass (MM). After averaging, the data obtained were subjected to multivariate analysis using the average Euclidean distance in Genes software. The dendogram obtained through the UPGMA mean distance clustering method formed two groups. One formed by population 1 and another group formed by populations 2, 3 and 4. The value of the cohenetic correlation (CCC) found was 0.9446, which showed a high adjustment between the data of the dissimilarity matrix and the dendrogram obtained by the method (UPGMA). The variable MP presented the greatest contribution to dissimilarity, followed by the variable NFI, successful by the variables FED, FM and FLD.